2011
DOI: 10.1007/s12206-010-1223-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field effect on fluid flow characteristics in a pipe for laminar flow

Abstract: The influence of a magnetic field on the skin friction factor of steady fully-developed laminar flow through a pipe was studied experimentally. A mathematical model was introduced and a finite difference scheme used to solve the governing equations in terms of vorticity-stream function. The model predictions agree favourably with experimental results. It is observed that the pressure drop varies in proportion to the square of the product of the magnetic field and the sine of the magnetic field angle. Also, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…The effect of the magnetic field normal to the flow direction imposes rise to a resistive force. Also, it has the tendency to slow down or suppress the movement of the liquid in the pipe (this is consistent with results reported by Malekzadeh et al (2011), Lie et al (1989)). There results demonstrated that the maximum magnitude, of both, global and local velocities was decreased with increasing of the magnetic Bond number, which, in turn reduces the motion of the gas bubbles.…”
Section: Effect Of the Magnetic Field (Ha) On (Diesel-cng) Velocity Isupporting
confidence: 91%
See 1 more Smart Citation
“…The effect of the magnetic field normal to the flow direction imposes rise to a resistive force. Also, it has the tendency to slow down or suppress the movement of the liquid in the pipe (this is consistent with results reported by Malekzadeh et al (2011), Lie et al (1989)). There results demonstrated that the maximum magnitude, of both, global and local velocities was decreased with increasing of the magnetic Bond number, which, in turn reduces the motion of the gas bubbles.…”
Section: Effect Of the Magnetic Field (Ha) On (Diesel-cng) Velocity Isupporting
confidence: 91%
“…Gedik et al (2012) studied the unsteady viscous incompressible and electrically conducting of two phase fluid flow in circular pipes with external magnetic and electrical field. The influence of a magnetic field on the skin friction factor of steady fully-developed laminar flow through a pipe was studied experimentally by Malekzadeh et al (2011), it was found that a transverse magnetic field changed the axial velocity profile from parabolic to a relatively flat shape, Chamkha and Ahmed (2011) explained that increasing the value of magnetic field parameter resulted in increment in the skin-friction coefficients while, the velocity components decreased with the increasing values of the magnetic parameter. Kumar et al (2012) have solved the problem of steady, laminar flow and heat transfer of an electrically conducting fluid through vertical channel in the presence of uniform transverse magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Malekzadeh et al [40] applied a mathematical model and a finite difference scheme to solve the governing equations of the laminar flow through a circular MHD channel. They offered an approximate mathematical expression for estimating the magnetic entrance length as a function of Hartmann number, sinus of the magnetic field angle, Reynolds number and the pipe diameter.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lundgren et al inspected the behavior of non‐Newtonian Hartmann flow. Malekzadeh et al studied the impact of magnetic field in a pipe for fully developed steady and laminar flow. They reported that the magnetic field affected the axial velocity distribution bringing flatten rather than the parabolic distribution.…”
Section: Introductionmentioning
confidence: 99%